Characterization of gas-liquid two phase flows using dielectric Sensors. (October 2015) - Arunkumar, S.; Adhavan, J.; Venkatesan, M.; Das, S.K.; Balakrishnan, A.R.
Abstract: Two phase flow regime identification and void fraction measurement is an area of considerable interest because of its wide applications in process industries. The principle involved in dielectric measurement is that the two phase flow regime is characterized by the changes in effective permittivity of the two phase fluid mixture. In the present work, a pair of parallel copper electrodes on the two sides of a glass tube acts as a dielectric sensor. As the void fraction in the glass tube changes, the effective permittivity of the medium changes. This causes a variation in the capacitance value across the electrodes. A standard IC, Oscillator 555 is employed as a tool to generate a rectangular wave. The variation in dielectric constant is analyzed based on the change in time period of the trough (T0 ) of the rectangular wave that is recorded online by a data acquisition system. Experiments were performed in a 4.7 mm diameter tube with air-water, air-palmolein oil two phase fluids to study the variation in dielectric constant which is indicated as a change in time period of trough. The effect of conductivity of water on the capacitance variation is examined with water having Total dissolved solids (TDS) which is a measure of movable ions in the range 10-4000 ppm (16 µS/cm–6.3 mS/cm). The novelty in the present work is the determination of changes in capacitance value based on the change in time of trough of the rectangular wave. The technique does not require amplification or a filtering circuit, thereby leading to a precise identification of two phase flow regime. Highlights: Two phase flows. Dielectric Sensor. Time of Trough. Void Fraction.